2015
DOI: 10.1007/s11182-015-0419-7
|View full text |Cite
|
Sign up to set email alerts
|

On the Stability of a Nonlinear Oscillator with Higher Derivatives

Abstract: The stability of a Pais-Uhlenbeck nonlinear oscillator with higher derivatives is examined. The stability of the linear theory is demonstrated and a nonlinearity preserving the stability of the system is found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 24 publications
(35 reference statements)
0
38
0
Order By: Relevance
“…This fact has been established in [10,11] (see also Ref. [12]) where the corresponding families of Hamiltonian structures have been constructed. The main advantage of the alternative Hamiltonian formulation obtained in such a way is that this may correspond to a positive-definite Hamiltonian.…”
Section: Introductionmentioning
confidence: 75%
“…This fact has been established in [10,11] (see also Ref. [12]) where the corresponding families of Hamiltonian structures have been constructed. The main advantage of the alternative Hamiltonian formulation obtained in such a way is that this may correspond to a positive-definite Hamiltonian.…”
Section: Introductionmentioning
confidence: 75%
“…We suppose that we have the coordinates x µ , µ = 0, 1, 2 such that x i , i = 1, 2 are the space coordinates, while x 0 is the time. The ADM variables (17), (18), (19) are very convenient to describe the metric once the spacetime is decomposed in space and time.…”
Section: The First Order Formulationmentioning
confidence: 99%
“…It has been also found that the interactions can be included into the PU equations leaving the dynamics stable [1]. Furthermore, the stable higher derivative PU equation with interaction still admits Hamiltonian formulation in the corresponding first order formalism, though the stable vertices are non-Lagrangian in the higher derivative equations of motion [19].One of the frequently discussed higher derivative field theories is the third order extension of Chern-Simons [20]. It has * g kl ( F 0 F 0 + * g sr F s F r ) .…”
mentioning
confidence: 99%
“…It is also worth to notice that the PU oscillator equation of motion admits the interaction vertices such that do not spoil the classical stability [19,39]. These vertices are nonLagrangian, while the interacting higher-derivative equations, being brought to the first-order formalism, still remain Hamiltonian with positive Hamilton function [23,24]. In this way, the PU oscillator equation admits inclusion of interactions such that leave the dynamics stable beyond the free level and admit Hamiltonian formulation.…”
Section: Introductionmentioning
confidence: 98%
“…Also notice that all the considered examples [19,22] of stable higher-derivative models admit the interactions such that do not spoil classical stability. Further examples of stable interactions can be found in [23][24][25] for various higher-derivative models. In all these models, the canonical energy is unbounded at free level, while the stability is due to another bounded conserved quantity.…”
Section: Introductionmentioning
confidence: 99%